Attempt at Doubt. The Abandonment of Aesthetic Automatisms Through Collective Exercises in the Performative Practice by Didymos - Tikhomirova, Yulia S. (Aisthesis, 2024)
The research examines how contemporary performance art challenges aesthetic habits, which often manifest as disruptive and constraining elements within imaginative faculties. The Italian duo Didymos focuses its oeuvre on deconstructing routine and unintentional behaviors. The artists employ a series of performative practices involving the audience in a political experience by implementing the category of doubt. Together, they engage in the execution of the most mundane actions, with the overarching objective of dismantling layers of conventional knowledge. This process entails a deliberate departure from sensible automatism, ultimately facilitating an escape from arguably apolitical modes of engaging with the world. The essay explores Didymos’s recent artistic practice, A Social Gym, confronts the category of doubt used by the duo with Jacques Rancière’s concept of dissensus, and attempts at tracing the bind between aesthetic norms and artistic expressiveness from the perspective of the aesthetics-politics relationship.